How do 1st year graduate students search information at School of Industrial Studies and Management of the Polytechnic Institute of Porto? - Martins, Susana (2017)
Higher Education Institutions (HEI) should enable students with expertise in different areas of knowledge and soft skills so that they become empowered to properly deal with pressing issues of an information era, and act according to the changes promoted by the implementation of Bologna Declaration. The HEI educate much of the labor force and that is why they must also assume responsibility in this training sphere, giving their student body with skills of Information Literacy (IL). Effectively to achieve this, all the actors of the teaching and learning process should have an active role, although on different scales. A partner of such an approach will undoubtedly be the library and the actions that it can develop so that students can effectively provide themselves with such skills. On that basis a descriptive research was conducted that assumed the following objectives: a) know the information search habits of students of 1st year of all undergraduate courses at the School of Industrial Studies and Management (ESEIG) of the Polytechnic Institute of Porto IPP) (daytime degrees); b) assess compliance and impact of training activities implemented by the ESEIG-IPP Library in the field of information search. Data collection was based on a questionnaire created in Limesurvey. The results show that the most commonly used sources of information are the slides that teachers provide, followed by colleagues appointments. Still the general use of the Internet and the use of search engines are elements that characterize this student population as a whole. Despite the diminutive use of this community regarding the academic and scientific resources that the institution subscribes and offers, there is an awareness of the importance of having access to such resources, even more by the use of a Virtual Private Network (VPN). Some elements of this community say that four months after the class started they never went to the library of the institution because they never needed it. With regard to training activities provided by the library, they appear to have little adhesion within this group of students and several reasons are shown to explain why that happens. But those who attended these activities assume they were satisfactory and that had a positive impact on their academic performance. This study showed that there are students who do not consider important or pertinent to know how to validate information sources and information, to know how to use the b-on (library of knowledge online – a database aggregator subscribed by institutions of higher education, research and others) and their bibliometric indicators or even to know how to manage the references and citations. We conclude that there is much work to be done, not only within this community, but also with the Presidency of ESEIG-IPP and the school faculty, that have a pertinent role in this matter, since there seems to be some alienation on the part of these students to relevant issues in the education sector and society information, and that will have a direct and immediate impact on their academic performance, but also in other individual spheres. It will therefore be necessary to develop an awareness campaign to the student body of the institution so that everyone can be informed about the importance that these issues have in these different contexts, and the library is a partner in this way.